Finance and Development March 2016. (Finance and Development; Finance and Development ;, 2016)
This article profiles economist David Card, whose work on minimum wages, immigration, and education challenged conventional wisdom. Card rose to prominence in 1995 when he won the coveted John Bates Clark Medal, then awarded every two years by the American Economic Association to the leading economist under the age of 40 who is working in the United States. It is considered the top award in economics barring the Nobel Prize. Through empirical research into a series of 'natural experiments'-real-life situations underpinned by robust data-Card challenged conventional economic thinking in several important areas. He found that, unlike in classical models, raising the minimum wage does not necessarily increase unemployment, and even has the potential to reduce it. More than 15 years of research led to a landmark 1993 paper and subsequent book-coauthored with Princeton professor Alan B. Krueger-that analyzed the impact of the minimum wage on the New Jersey fast-food industry.